Time Effectiveness and Performance of Employees in Complete Systematic Land Registration and Recognition of Rights at Land Office Kota Tangerang Selatan - Imas Masriah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aimed to determine the effectiveness of filing employee performance time and supporting and inhibiting factors of the Land Office at Kota Tangerang Selatan. This research was conducted for approximately 1 (one) year uses qualitative research with a SWOT analysis. The results showed that the implementation of the Land Office employees adhered to the standard operating system. The obstacles that occur are the lack of funds in its implementation and the lack of human resources. Supporting factors are the cost of free certificate ownership and good communication between the parties. Performance strategy of the South Tangerang City Land Office with EFE = 2.0900 and IFE = 2.0700. Also, to support the effectiveness of the performance of the South Tangerang City land office employees, among others, by increasing discipline, training employees to be familiar with the application of SOPs, interactive employees towards consumers can provide quality time management processes. Furthermore, time management in implementing the land certification program is carried out in collaboration with the community in granting land certificates directly, thus increasing public awareness because the program is carried out according to operational procedure standard and discipline.